Selective expression of two types of 28S rRNA paralogous genes in the chaetognath Spadella cephaloptera - Barthélémy, R.M.; Casanova, J.P.; Grino, M.; Faure, E. (Cellular and Molecular Biology, 2007)
Significant intra-individual variation in the sequences of the ribosomal RNA (rRNA) genes is highly unusual in animal genomes; however, two classes of both 18S and 28S rRNA gene sequences have been detected in chaetognaths, a small phylum of marine invertebrates. One species, Spadella cephaloptera Busch, 1851, is well-suited to the methods of in situ analysis of gene expression, since it is totally transparent. To test our hypothesis of a possible functional division of the two classes of genes, we carried out in situ hybridization. Our results indicated that 28S class II genes are expressed intensively in the oocytes of chaetognaths. In contrast, hybridization using an heterologous probe of 28S class I genes revealed only a single and relatively weak signal in a distinct area of intestinal cells. Our results suggest that the S. cephaloptera genome contains at least three different types of rRNA 28S genes; however, those which are expressed during housekeeping conditions could not be detected in our experiments.